Rozszerzony margines wypłacalności jako miara zagrożenia niewypłacalnością zakładów ubezpieczeń nie na życie - Bijak, Wojciech (Extended Solvency Margin as a Measure of the Insolvency Risk of Non-Life Insurance Companies, 2006)
The law regulations in EU countries including Poland use the solvency margin as a basic measure of the insolvency risk of insurance companies. The solvency margin could be decomposed to a model and a scale of safety. Such decomposition gives a possibility to generalize the solvency margin concept and allows to take into consideration the different risk factors of insurance activity connected with e.g. the insurance portfolio and the investment portfolio. This paper concerns a concept of the extended solvency margin. A proposed method of the extended solvency margin (ESM) assessment allows us to consider the different technical, investment and other risk factors of insurance activity. The introduced concept of a scale of safety allows the operating risk of an insurance company to be expressed in terms of capital requirement. The risk of insolvency is analyzed in an annual time perspective. The theoretical discussion is illustrated with an empirical example derived from non-life insurance companies operating as joint stock companies in Poland in the period 1995-2002.The law regulations in EU countries including Poland use the solvency margin as a basic measure of the insolvency risk of insurance companies. The solvency margin could be decomposed to a model and a scale of safety. Such decomposition gives a possibility to generalize the solvency margin concept and allows to take into consideration the different risk factors of insurance activity connected with e.g. the insurance portfolio and the investment portfolio. This paper concerns a concept of the extended solvency margin. A proposed method of the extended solvency margin (ESM) assessment allows us to consider the different technical, investment and other risk factors of insurance activity. The introduced concept of a scale of safety allows the operating risk of an insurance company to be expressed in terms of capital requirement. The risk of insolvency is analyzed in an annual time perspective. The theoretical discussion is illustrated with an empirical example derived from non-life insurance companies operating as joint stock companies in Poland in the period 1995-2002.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 17-33